2013
DOI: 10.5455/oams.020313.or.028
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and chemopreventive potentialities of fenugreek (Trigonella foenum graecum) seed extract

Abstract: Phytochemicals present in plant foods have been linked to reduce several chronic diseases including cancer. They have gained popularity as safer and cheaper alternative to conventional drugs. We studied the antimutagenic and anticarcinogenic activity of Trigonella foenum graecum (L.) seed (TFGS) extract using Salmonella microsomal assay and two stage skin papilloma model in mice, respectively. Different concentrations (2.5, 5, 10 and 20 g/100 ml of distilled water) of the aqueous seed extract of fenugreek were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Fenugreek seed administration and its extracts significantly decreased plasma cholesterol, triglyceride, and LDL cholesterol. However, HDL cholesterol level was found to be constant; that is, no effect was registered on it [ 45 ].…”
Section: Fenugreek As Potential Therapeutic Agent Against Several mentioning
confidence: 99%
“…Fenugreek seed administration and its extracts significantly decreased plasma cholesterol, triglyceride, and LDL cholesterol. However, HDL cholesterol level was found to be constant; that is, no effect was registered on it [ 45 ].…”
Section: Fenugreek As Potential Therapeutic Agent Against Several mentioning
confidence: 99%
“…The present investigation is supported by the work of Qureshi et al, (2015); they investigated the ethonlic extract of fenugreek seed at the rate of 0.5 mg/ml against the E. Coli and found 2.1mm inhibition. Antimutagenic and chemopreventive study was carried out by Chatterjee et al, (2013) in mice by using skin papilloma as a model. They observed that water based extract of fenugreek seeds at rate of 20 g/ml showed strong inhibition against the mutagenes in different strains of salmonella.…”
Section: In-vitro Antimicrobial Activities Of Phyto-pro-bioticsmentioning
confidence: 99%
“…The vitamin prevents cardiovascular diseases (CVDs) by reducing platelet adhesion, elevating High density Lipoprotein (HDL) level in the blood and inhibiting smooth muscle cell proliferation, a predisposing factor in atherosclerosis (Lee, et al 2005). They are readily available, cheaper and safer, nutraceuticals, functional foods and value added food products are becoming widely acceptable as alternatives to conventional drugs and pharmaceuticals (Chatterjee, Goswami, Bhatnagar and Kumar, 2013).…”
Section: Empowerment Of Youths For Sustaining National Stability In N...mentioning
confidence: 99%